Bursa Kerja Khusus’s Strategic Role in Curriculum-Industry Synchronization for Graduate Competence - Mari'atul Kamila Ramadhan; Ahmad Yusuf Sobri; Juharyanto Juharyanto (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
Vocational education plays a strategic role in preparing skilled workers who meet the demands of the international market. This study aims to analyze the determinants that influence the competency levels of vocational graduates in the context of global competition. This research uses a Systematic Literature Review (SLR) approach, a method that allows for the identification, assessment, and synthesis of all previous research findings comprehensively and systematically based on specific research questions. The findings include strategies designed by schools and specialized job markets with the aim of improving employability, including link and match, industrial work practice (internship), competency skill examinations, curriculum synchronization, and the ability to collaborate and communicate across cultures. The identified skill gaps include deficiencies in the abilities of teachers or educators, inadequate facilities and infrastructure, and a lack of industry partner The implication is that improving the global competitiveness of vocational graduates necessitates continuous efforts to revitalize and develop educational programs through deeper integration with the realities and needs of the global industry. Thus, graduates of vocational education can be optimized as human capital who are not only technically competent but also adaptive and competitive in facing the complexities of the global labor market.